2012
DOI: 10.1161/circimaging.111.967810
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Injury in ST-Elevation Myocardial Infarction

Abstract: Background-Patients with right ventricular injury (RVI) complicating ST-elevation myocardial infarction (STEMI) haveimpaired prognosis, but it is unclear which patients are at risk of developing RVI. Cardiac magnetic resonance can identify these patients and might add important information on risk stratification, prognosis, and treatment. Aims were to determine the predictors and the prognostic significance of RVI assessed by wall motion abnormalities, edema, myocardial salvage index, and delayed enhancement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 30 publications
0
23
0
3
Order By: Relevance
“…31,32 of concomitant LV involvement, this study indicated that the mean optimal PWP, which corresponded to the maximum LV stroke work index in each patient, was 16 mmHg.…”
Section: Volume Replacementmentioning
confidence: 58%
See 1 more Smart Citation
“…31,32 of concomitant LV involvement, this study indicated that the mean optimal PWP, which corresponded to the maximum LV stroke work index in each patient, was 16 mmHg.…”
Section: Volume Replacementmentioning
confidence: 58%
“…22 However, although the number of patients with RV infarction is small, these patients seem to have a higher risk of in-hospital mortality in the mechanical reperfusion era than during the fibrinolytic era. Figure 2 shows the changes in the in-hospital mortality rate and relative risk of RV infarction for in-hospital mortality between the fibrinolytic and mechanical reperfusion era; 8,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] An increase in the relative risk of RV infarction from 2.29 (95% CI 1.67-3.14) to 2.98 (95% CI 1.41-6.31) also occurred during this period. The precise explanation for the paradox remains unknown.…”
Section: Short-term Prognosismentioning
confidence: 99%
“…[22] Contrast enhanced CMR imaging allows for superior identification of right ventricular infarcts. [2327] Right ventricular injury is not limited to inferior infarcts, but can be found in anterior infarcts as well. [23] A recent study showed that the right ventricle was involved in 46% of patients with inferior infarcts and 30% of anterior infarcts.…”
Section: Discussionmentioning
confidence: 99%
“…Эти изменения структуры стенки ЛЖ, объемов и формы (геометрии) камер сердца часто пред-шествуют клиническому проявлению синдрома сер-дечной недостаточности, являются предвестниками декомпенсации сердечной деятельности и отрица-тельно влияют на качество жизни и выживаемость больных [14]. При ИМ ПЖ восстановительный процесс менее сложен и сопровождается улучшением сокра-тительной способности ПЖ [15]. Функциональное вос-становление ПЖ уменьшает летальность больных ИМ нижней стенки ЛЖ и ПЖ [16].…”
Section: Discussionunclassified